Evaluation of Anti-inflammatory Activity of Mixture of Kencur Extract (Kaempferia galanga L.) with Glucosamine and Chondroitin In Vivo in Mice (Rattus Novergicus) - Masyrobatin, Masyrobatin; Paramita, Angggun Putri; Sukardiman, Sukardiman; Suharjono, Suharjono (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Glucosamine and chondroitin are commonly used in osteoarthritis therapy and are classified as SYSADOA. Both act as chondroprotective and anti-inflammatory agents, though their efficacy remains debated. Efforts have been made to enhance their anti-inflammatory effects by combining them with Kaempferia galanga L. (kencur) extract. This study aims to evaluate the anti-inflammatory effectiveness of a combination of kencur extract, glucosamine, and chondroitin in vivoin rats (Rattus norvegicus). The anti-inflammatory activity was tested on male white Wistar rats using the paw edema test. The increase in paw volume was measured and converted into the percentage of edema inhibition. Histopathological analysis to count neutrophil inflammatory cells was performed using Hematoxylin and Eosin (HE) staining. Data analysis was conducted on both the percentage of edema inhibition and the neutrophil cell counts. The results showed that the combination of glucosamine (45 mg/kg BW) and chondroitin (36 mg/kg BW) with kencur extract at doses of 600 mg, 900 mg, and 1200 mg/kg BW exhibited anti-inflammatory activity. The combination with 600 mg/kg BW of kencur extract showed a specific percentage of edema inhibition. The combination of glucosamine and chondroitin with 900 mg/kg BW of kencur extract showed the best anti-inflammatory activity, which was equivalent to 1200 mg/kg BW of kencur extract and superior to the effects of glucosamine and chondroitin alone.